Pediatric asthma symptom control during lockdown for the COVID‐19 pandemic in Spring 2020: A prospective community‐based study in Cyprus and Greece. Issue 2 (24th November 2021) - Kouis, Panayiotis; Michaelidou, Eleni; Kinni, Paraskevi; Michanikou, Antonis; Anagnostopoulou, Pinelopi; Dimitriou, Helen; Karanicolas, Kostas; Matthaiou, Andreas M.; Achilleos, Souzana; Papatheodorou, Stefania I.; Koutrakis, Petros; Middleton, Nicos; et al.
Abstract: Objectives: To prospectively quantify at the community level changes in asthma symptom control and other morbidity indices, among asthmatic schoolchildren in response to coronavirus disease 2019 (COVID‐19) lockdown measures. Methods: In Spring 2019 and Spring 2020, we prospectively assessed monthly changes in pediatric asthma control test (c‐ACT), asthma medication usage, infections and unscheduled visits for asthma among schoolchildren with active asthma in Cyprus and Greece. We compared asthma symptom control and other morbidity indices before and during lockdown measures, while participants' time spent at home was objectively assessed by wearable sensors. Results: A total of 119 asthmatic children participated in the study during Spring 2020. Compared to a mean baseline (pre‐COVID‐19 lockdown) c‐ACT score of 22.70, adjusted mean increases of 2.58 (95% confidence interval [CI]: 1.91, 3.26, p < 0.001) and 3.57 (95% CI: 2.88, 4.27, p < 0.001) in the 2nd and 3rd monthly assessments were observed after implementation of lockdown measures. A mean increase in c‐ACT score of 0.32 (95% CI: 0.17, 0.47, p < 0.001) was noted per 10% increase in the time spent at home. Improvement was more profound in children with severe asthma, while significant reductions in infections, asthma medication usage and unscheduled visits for asthma were also observed. During Spring 2019, 39 children participated in the study in the absence of lockdown measures and no changes in c‐ACT or other indices of disease severity were observed. Conclusions: Clinically meaningful improvements in asthma symptom control, among asthmatic schoolchildren were observed during the COVID‐19 lockdown measures in Spring 2020. Improvements were independently associated with time spent at home and were more profound in the children with severe asthma.